Transceiver Optimization for DF MIMO Relay Systems with a Wireless Powered Relay Node - Li, Bin; Cao, H.; Rong, Yue; Su, T.; Yang, G.; He, Z. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
In this paper, a two-hop decode-and-forward (DF) multiple-input multiple-output (MIMO) relay system is investigated, where the relay node harvests the radio frequency energy transmitted by the source node and uses the harvested energy to forward information from source to destination. We consider both the time switching (TS) and power splitting (PS)-based protocols between wireless information and energy transfer. For each protocol, we study the optimal source and relay covariance matrices to maximize the source-destination mutual information (MI), under the source energy constraint and the harvested energy constraint at the relay node. For the TS protocol, the peak transmission power constraints are also considered at the source and relay nodes. The numerical results are presented to demonstrate the effectiveness of the proposed methods. It is shown that the proposed DF relay system achieves a higher MI than that of the amplify-and-forward relay system. Moreover, the PS-based protocol achieves a higher system MI than the TS-based protocol, but at a higher computational complexity.